High sex ratios and household portfolio choice in China - LI, Wenchao (Institutional Knowledge at Singapore Management University, 2022)
This paper studies how high sex ratios (more men than women) affect household portfolio choice. Using data from a nationally representative Chinese household finance survey, we find that a 1 standard deviation increase in the sex ratio would raise the stock market participation rate by 2.9 percentage points or 52.2 percent for families with a son relative to families with a daughter. Our estimates imply that rising sex ratios explain around 10 percent of the significant growth in China’s stock market size in recent decades.